Synthesis, characterisation and crystal structure of a novel pyridyl urea macrocycle. (1st December 2016) - Perveen, Shagufta; Kilburn, Jeremy; Al-Taweel, Areej; Light, Mark
A novel pyridyl urea based macrocycle has been synthesised and fully characterised including a single crystal X-ray structure determination. The synthetic approach first involves the reaction of benzyloxycarbonylaminopropyl-3-isocyanate with t-butyl 2-[(2-aminopyridin-3-yl)oxy]acetate resulting in a coupling product. After deprotection of the amine and acid moieties and coupling subsequent coupling in the presence of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), a macrocycle is formed. The structures of the compounds were confirmed by mass spectrometry and NMR spectroscopy. The X-ray crystal structure of the macrocycle reveals as expected a non-binding conformation with an intramolecular hydrogen bond between the urea NH and the pyridyl nitrogen.